EKSPLANASI APLIKASI LEARNING ORGANIZATION PADA INSTITUSI PUBLIK MELALUI PEMBELAJARAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT II - Priyatno, Makhdum (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
Learning Organization (LO) has now its own discipline. This has led LO so popular and crucial among learners both from private and public sectors. LO discipline consists of: Systems Thinking, Personal Mastery, Mental Models, Building Shared Vision, and Team Learning. LO can be applied both in private and public sectors. In order to achieve LO’s goals, it is necessary to comprehend its methods, techniques, and strategies. The implementation of LO in public institutions requires specific approaches. Methods for introducing LO in public institutions may vary depending on the contexts, for example specific package of the five-discipline education & training for staff, the five-discipline training as a part of education & training package, policy regarding the deployment of the fivediscipline from the head of the institution to be put into action, and many other methods. This writing describes the implementation of LO at public institutions through Structural Leadership Training II. A variety of methods for implementing LO are presented for class or group works. At the end of the training, participants are expected to be able to understand and developlearning organization based on the contexts where they work. They are also expected to be the main actors of LO and the prime moving force for its permanent system.